Digital transformation technology in the insurance service in the National Insurance Company and the Iraqi General Insurance Company : applied research (Journal of Accounting and Financial Studies ( JAFS ), 2023)
The aim of this research is to identify the impact of the effectiveness of digital transformation technology in improving the efficiency of the insurance service in the public insurance companies in Iraq through digital transformation technology in the insurance process "promotion of the insurance product, submission of insurance application, underwriting, settlement of losses" and to achieve this goal a questionnaire was designed A survey distributed in the surveyed community Which represents the decision makers in the researched companies under study, and one of the most important results of the research was the existence of a relationship between digital transformation and improving the efficiency of the insurance process, whether through promoting the insurance policy, submitting an insurance application, underwriting, or settling compensation. The study recommended the importance of adopting legal legislation related to public insurance companies and developing The infrastructure of information technology and digital transformation, which forms the basis of digital transformation service, and the importance of educating all workers in insurance companies and training them on the use of digital transformation, especially computers, the Internet, software and applications, in line with current developments.